Global monopole as a generator of a bulk-brane structure in Brans–Dicke bulk gravity - Caramês, Thiago R. P.; da Silva, J. M. Hoff [UNESP] (Springer Nature, 2020)
We investigate a braneworld model generated by a global monopole in the context of Brans–Dicke gravity. After solving the dynamical equations we found a model capable to alleviate the so-called hierarchy problem. The obtained framework is described by a hybrid compactification scheme endowed with a seven-dimensional spacetime, in which the brane has four non-compact dimensions and two curled extra dimensions. The relevant aspects of the resulting model are studied and the requirements to avoid the well known seesaw-like behavior are discussed. We show that under certain conditions it is possible to circumvent such a pathological behavior that characterizes most of the models that exhibit hybrid compactification. Lastly, we deepen our analysis by considering possible extensions of this model to a setup with multiple branes and orbifold-like extra dimension. For this, we compute the consistency conditions to be obeyed by this more general configuration as predicted by the braneworld sum rules formalism. This study indicates the possibility of exclusively positive brane tensions in the model.